2022
DOI: 10.3390/ma15134716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Elastic, Piezoelectric, and Dielectric Properties of Lithium Niobate from 25 °C to 900 °C Using Electrochemical Impedance Spectroscopy Resonance Method

Abstract: Lithium niobate (LiNbO3) is known for its high Curie temperature, making it an attractive candidate for high-temperature piezoelectric applications (>200 °C); however, the literature suffers from a paucity of reliable material properties data at high temperatures. This paper therefore provides a complete set of elastic and piezoelectric coefficients, as well as complex dielectric constants and the electrical conductivity, for congruent monocrystalline LiNbO3 from 25 °C to 900 °C at atmospheric pressure. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The directly measured dielectric constants usually show strong frequency and temperature dependences in radio frequencies. [ 59,60 ] Alternatively, they can also be estimated from Raman spectrum by using the Lyddane–Sachs–Teller relations ε11S=ε11E[ ωiLOωiTO ]2 and ε33normalS=ε33A1[ ωiLOωiTO ]2 [ 61 ] and correctly assigned observed phonon frequencies of LO and TO modes. One obtains ε11normalS=40.75 and ε33normalS=23.67, which show much better agreement with our calculated results.…”
Section: Resultsmentioning
confidence: 99%
“…The directly measured dielectric constants usually show strong frequency and temperature dependences in radio frequencies. [ 59,60 ] Alternatively, they can also be estimated from Raman spectrum by using the Lyddane–Sachs–Teller relations ε11S=ε11E[ ωiLOωiTO ]2 and ε33normalS=ε33A1[ ωiLOωiTO ]2 [ 61 ] and correctly assigned observed phonon frequencies of LO and TO modes. One obtains ε11normalS=40.75 and ε33normalS=23.67, which show much better agreement with our calculated results.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was shown that it may be overcome by operating at a high frequency (>MHz) and choosing a monocrystal or a stoichiometric element [ 16 ]. The complete set of elastic, piezoelectric and dielectric coefficients has been evaluated from room temperature to 900 C [ 17 , 18 ]. The selected material, 36 Y-cut LiNbO (from MTI Corporation), was chosen because its thickness vibration mode is quasi-extensional, with the geometry selected to ensure maximum resonance at the desired mode and minimal at other modes.…”
Section: Transducer Designmentioning
confidence: 99%
“…From a review of different electrodes for high-temperature sensors [ 21 ], platinum was selected and the supplier (INRS) offered to add a layer of titanium to ensure better adhesion of the platinum. The range of thickness for electrodes is around 100 nm, so 100-nm-thick platinum electrodes were deposited with a 20 nm titanium adhesion layer onto the piezoelectric element by physical vapor deposition and were usable up to 900 C [ 18 ]. The type of deposition selected was thermal and electron beam deposition.…”
Section: Transducer Designmentioning
confidence: 99%
“…To verify the existence of SAWs on the LN-on-SiC composite substrate and to determine the operating frequencies of the designed device and phononic crystal, we investigated the mechanical wave distribution on the surface of the 0.3 µm thick LN film deposited on the SiC substrate. Material parameters (LN [50] and SiC [51]) are shown in supplemental information. The LN single crystal film is x-cut, with the direction of SAW propagation being in the y-direction of the crystal.…”
Section: Quasi-single-mode Excitation Of Love Waves On Ln-on-sic Subs...mentioning
confidence: 99%